Adsorption of Phosphate in Synthetic Laundry Wastewater using Empty Palm Oil Fruit Bunch - Ariani, Ismi Khairunnissa; Anifah, Eka Masrifatus; Hudayarizka, Riza; Paramita, Fika (Universitas Negeri Malang, 2024)
The laundry wastewater contains phosphates that can lead to eutrophication. Treatment of laundry wastewater with phosphate concentration can be done physically or chemically. The adsorption method was selected due to its high efficacy, and economical operation. Activated carbon derived from Empty Palm Oil Fruit Bunch (EPOFB) biomass waste was utilized as the adsorbent, leveraging its lignocellulosic components such as cellulose, hemicellulose, and lignin, that can adsorb pollutants. This study aims to assess the impact of adsorbent dosage and contact time on the adsorption capacity and phosphate removal efficiency. The activated carbon was produced from EPOFB via carbonization and activation processes at 400°C and KOH 6M. The variables including adsorbent dosage and contact time, ranging from 0.2 to 1.0 g/100mL and 20 to 100 minutes, respectively. Results indicate that the adsorbent dosage affects phosphate removal from synthetic laundry wastewater, while contact time does not significantly impact removal efficiency. The highest removal efficiencies of 67.37% and 70.03% were achieved at optimal doses of 8 g/L and 10 g/L, respectively, with contact times of 20 and 80 minutes. The isotherm model and kinetics of phosphate adsorption onto synthetic laundry wastewater using EPOFB adsorbent were identified as Freundlich and pseudo-second order, respectively.